Protozoan Predation of Escherichia coli O157:H7 Is Unaffected by the Carriage of Shiga Toxin-Encoding Bacteriophages - Schmidt, Carrie E.; Shringi, Smriti; Besser, Thomas E. (PloS one, 2016)
Escherichia coli O157:H7 is a food-borne bacterium that causes hemorrhagic diarrhea and hemolytic uremic syndrome in humans. While cattle are a known source of E. coli O157:H7 exposure resulting in human infection, environmental reservoirs may also be important sources of infection for both cattle and humans. Bacteriophage-encoded Shiga toxins (Stx) carried by E. coli O157:H7 may provide a selective advantage for survival of these bacteria in the environment, possibly through their toxic effects on grazing protozoa. To determine Stx effects on protozoan grazing, we co-cultured Paramecium caudatum, a common ciliate protozoon in cattle water sources, with multiple strains of Shiga-toxigenic E. coli O157:H7 and non-Shiga toxigenic cattle commensal E. coli. Over three days at ambient laboratory temperature, P. caudatum consistently reduced both E. coli O157:H7 and non-Shiga toxigenic E. coli populations by 1-3 log cfu. Furthermore, a wild-type strain of Shiga-toxigenic E. coli O157:H7 (EDL933) and isogenic mutants lacking the A subunit of Stx 2a, the entire Stx 2a-encoding bacteriophage, and/or the entire Stx 1-encoding bacteriophage were grazed with similar efficacy by both P. caudatum and Tetrahymena pyriformis (another ciliate protozoon). Therefore, our data provided no evidence of a protective effect of either Stx or the products of other bacteriophage genes on protozoan predation of E. coli. Further research is necessary to determine if the grazing activity of naturally-occurring protozoa in cattle water troughs can serve to decrease cattle exposure to E. coli O157:H7 and other Shiga-toxigenic E. coli.